Opportunistic and other intestinal parasites infections among HIVpositive patients in the era of combination antiretroviral therapy and preventive treatment in Ouagadougou, Burkina Faso - Adama Zida; Abdourahamane Yacouba; Marcel P Sawadogo; Ismael Diallo; Ibrahim Sangare; Sanata Bamba; Bassory Ouattara; Tinga R Guiguemde (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2017)
Background: One of the particularities of human immunodefi ciency virus (HIV) infection in the tropics is its frequent association with parasitic diseases so frequent in this area. Aim: The aim of this study was to update the epidemiological and clinical profi le of intestinal parasites among HIV-positive patients in the era of combination antiretroviral therapy (ART) and preventive treatment in Ouagadougou, Burkina Faso. Materials and Methods: A cross-sectional study was conducted in a single health care system, Yalgado Ouédraogo University hospital, between January 2013 and December 2014. A total of 131 HIVinfected patients were included in the study. Blood and Stool samples were collected for CD4 counts and for intestinal parasitic examination using direct, formol-ether concentration, a concentration method using sodium chloride solution, modifi ed Ziehl-Neelsen and Weber modifi ed trichrome. Odds ratio was calculated to estimate the risk attributable to different factors with confi dence intervals. Chi-square (X2)  or Fisher's Exact Test statistical analysis was used to test level of signifi cance at p<0.05 using SPSS 20.0.0. Results: A prevalence of 73.3% of intestinal parasites was recorded. Most of the parasitic infections were protozoa (97.9%) with few helminths (2.1%). Cryptosporidium spp. (29.2%), was the most commonly found parasite followed by Entamoeba coli (23.9%) and Isospora belli (21.9%). There were 76 cases (78.5%) of single infection and 20 cases (21.5%) of mixed infection. Paradoxically, patients who use preventive treatment were more infected with opportunistic parasites (p= 0.05, OR=2.16, 95% CI= 1.06-4.40). In multivariate analysis, patients with diarrhea (OR=4.04, 95% CI=1.94-8.41), and illiterate (OR=3.70, 95% CI=1.68-8.14) had higher risk of opportunistic parasites. The diarrheic patients were 0.29 times more likely to be infected with opportunistic parasites. Conclusion: Despite the advent of combination ART and preventive treatment of opportunistic infections, intestinal parasites remain very prevalent and associated with diarrhea among patients with HIV in Ouagadougou.